THE ROLE OF REAL ESTATE PROMOTION IN THE PRODUCTION OF PROMOTIONAL DWELLINGS -MODELS IN THE URBAN ASSEMBLY OF CONSTANTINE - Cherif, Koua Mohamed; Hafid, Layeb (The journal of contemporary issues in business and government, 2023)
Real estate promotion is one of the mechanisms adopted by the public authorities to eliminate the housing crisis. The urban assembly of Constantine has known several public and private actors who have contributed significantly to the production of Promotional dwellings in different periods. The process of implementing housing in the urban assembly of Constantine was characterized by the involvement of many public actors (Office of Promotion and Real Estate Management OPGI), Fund National Savings and Reserve CNEP, National Real Estate Promotion Corporation ENPI ), and private actors representing various contractors and construction institutions. Through some models, we have studied and analyzed the various dwellings projects in the urban community of Constantine, in which the public and private sectors contributed, as the state relied on dividing dwellings projects into the two sectors, which led to the creation of a competitive field between them, which reflects positively on the residential area. It gives diversity to the urban fabric and even the quality of structures.